2019
DOI: 10.3390/ijms20092090
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor Markers with Antisense Peptides: An Example of Human Prostate Specific Antigen

Abstract: The purpose of this paper was to outline the development of short peptide targeting of the human prostate specific antigen (hPSA), and to evaluate its effectiveness in staining PSA in human prostate cancer tissue. The targeting of the hPSA antigen by means of antisense peptide AVRDKVG was designed according to a three-step method involving: 1. The selection of the molecular target (hPSA epitope), 2. the modeling of an antisense peptide (paratope) based on the epitope sequence, and 3. the spectroscopic evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 62 publications
(185 reference statements)
1
23
0
Order By: Relevance
“…The concept of sense and antisense (i.e., complementary) peptide interaction was developed in the early 1980s by Root-Bernstein, Biro, Blalock, Mekler, Siemion, and others [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. First, it was theoretically assumed and later empirically observed that peptides consisting of amino acids specified by sense and antisense sequences interact with higher probability and affinity than randomly selected peptides (Tables 1 and 2, Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The concept of sense and antisense (i.e., complementary) peptide interaction was developed in the early 1980s by Root-Bernstein, Biro, Blalock, Mekler, Siemion, and others [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. First, it was theoretically assumed and later empirically observed that peptides consisting of amino acids specified by sense and antisense sequences interact with higher probability and affinity than randomly selected peptides (Tables 1 and 2, Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Sense peptides are essential and specific parts of viral and other proteins that elicit normal and pathologic immune responses [6][7][8][9]14,[19][20][21]. Using antisense peptide technology, they could be utilized to derive targeted tests for different antibody (Ab), hormone, growth factor, or cell subpopulations [4][5][6][7][8][9]13,14,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations